Function of Vivid Coloration of Terrestrial Isopods from the Point of View of an Avian Predator - Barbora Ďurajková; Petr Veselý; Ivan Hadrián Tuf (Insects, 2025)
The ability of terrestrial isopods (Crustacea: Isopoda: Oniscidea) to protect themselves effectively from predation by birds has never been tested. They are equipped with glands producing chemical substances; moreover, some species show conspicuous coloration, which might suffice as an aposematic signal. We evaluated the palatability of isopods to birds. We tested the responses of Parus major captured in the wild (and thus possessing some experience with common native isopod species) to the following isopod species: Porcellio scaber (native, inconspicuous), Oniscus asellus (native, moderately conspicuous), Armadillo officinalis (non-native, moderately conspicuous), Armadillidium versicolor (native, conspicuous), and Armadillidium gestroi (non-native, conspicuous). We compared bird responses to isopods with reactions to the Blaptica dubia, an edible roach very similar to isopods in size and appearance. Isopods were better protected from bird attacks than roaches; however, their color pattern did not affect the level of protection. Birds were able to differentiate isopods from the roach; in experiments, where we presented isopod and roach individuals together, the birds hesitated longer in attacking and observed both prey items for a longer time. Non-native species either profited from the generalization of the protection of native isopods or from neophobia. Some isopods elicited significantly more discomfort behavior in birds, suggesting differences in the chemical protection among the tested species.